Knowledge Management Critical Success Factors in Construction Projects - Enshassi, Adnan; Falouji, Islam; AlKilani, Suhair; Sundermeieri, Matthias (International Journal of Sustainable Construction Engineering and Technology, 2016)
Knowledge management (KM) is defined as the act of establishing, sharing, and flowing of knowledge within an organization. Knowledge is an important driving force for business success and competiveness, especially in the construction industry, which is a project-based oriented that involves multidiscipline stakeholders. Knowledge management critical success factors (KMCSFs) are considered crucial for the construction industry. Previous works suggested a positive relation between addressing the critical success factors and the successful implementation of knowledge management. The objective of this paper is to identify and assess those factors. Data were collected by a structured questionnaire distributed randomly to 300 construction project professionals in the Palestinian construction industry concerning their knowledge management experiences. 277 questionnaires were received giving a response rate of 92%.Â Data were analyzed using Relative Importance Index (RII) and Exploratory Factor Analysis (EFA). It has been found that teamwork and face- to- face communication are considered the most significant critical success factors in managing knowledge. Moreover, three groups of critical success factors for managing knowledge have been categorized by EFA. They are related to culture, knowledge sharing process, and organizational structure. The findings of this study are significant in the understanding of knowledge management critical success factors in construction project. This knowledge may contribute to better decision-making and improvement of the construction projects performance.